2016
DOI: 10.21037/jtd.2016.08.25
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lymph node dissection during robotic-assisted lobectomy for non-small cell lung cancer: retrospective review of 159 consecutive cases

Abstract: Background:We investigated whether robotic-assisted surgery improves mediastinal lymph node dissection (MLND). Methods: We analyzed patients (pts) who underwent robotic-assisted video-assisted thoracoscopic surgery (R-VATS) lobectomy for non-small cell lung cancer (NSCLC) over 36 months. Perioperative outcomes, tumor histology, numbers, locations, and status of all lymph nodes (LNs), and TNM (tumor, nodal, and metastasis) stage changes were analyzed. Results: One hundred fifty-nine pts had mean tumor size 3.3±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Other studies have shown no differences in the numbers of LNs removed by robot-assisted procedures compared to VATS (22,24,26). However, our results showed a greater number of LNs harvested by robotic approaches in comparison to VATS approaches; this finding is consistent with prior publications that showed the superiority of robotic approaches in the number of retrieved LNs (27). Our ability to harvest lymph nodes also improved over time with the highest number of lymph node being harvested during the mature robot period.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies have shown no differences in the numbers of LNs removed by robot-assisted procedures compared to VATS (22,24,26). However, our results showed a greater number of LNs harvested by robotic approaches in comparison to VATS approaches; this finding is consistent with prior publications that showed the superiority of robotic approaches in the number of retrieved LNs (27). Our ability to harvest lymph nodes also improved over time with the highest number of lymph node being harvested during the mature robot period.…”
Section: Discussionsupporting
confidence: 90%
“…Most recently, the use of robotic lung surgery is increasing rapidly, and several studies have reported good experiences with LN dissection, and nodal upstaging ranging from 10% to 16.4%. [12][13][14]16,17 The relative ease of LN dissection is credited to the high-definition robotic camera and the wristed robotic instrumentation with increased freedom of motion and maneuverability in the chest. 18 In a multi-institutional effort, Wilson and colleagues 14 reported a rate of nodal upstaging of 10.9% for clinical stage I NSCLC that they compare favorably to historic VATS data.…”
Section: Discussionmentioning
confidence: 99%
“…First, our mean number of mediastinal (N2) LN stations reported was 3.7 ± 0.1 LN stations, with a total number of individual hilar and mediastinal (N1+N2) LNs being 13.4 ± 0.4 LNs. 36 These numbers with regard to our study groups are shown in Table 8. Mediastinal LN dissection has been one of the areas benefited by the robotic-assisted approach compared with conventional modalities.…”
Section: Discussionmentioning
confidence: 99%